Implementasi Appsheet Dalam Pengembangan Laporan Kerusakan Di PT. XYZ - Ahmad Fatihul Fuad (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
With the rapid development of technology, it benefits us in facilitating work in various fields. One example today is the use of modern technology in optimizing business processes. Information is one of the important assets for the Company in carrying out its business processes. With the rapid development of information technology also resulting in faster data movement, this must be used to help the Company in obtaining information quickly, precisely, effectively and efficiently. This is also evidenced by the increasing number of pioneering industries from small to large industries that are developing today. One of them is PT. XYZ. Of course, as a pioneering company, it requires a number of optimizations in its business process activities, one of which is reporting and recording. Because assets are one of the important elements in the Company's productivity, it is necessary to monitor the condition of assets regularly. The company still uses a manual asset damage reporting system using Whatsapp. Of course, this is less effective and efficient in the process, especially in recording activities to report damage to existing assets. Therefore, this study was conducted to help optimize the existing asset damage reporting system. From the results of the research, it can be seen using current technology, it can help optimize the reporting of damage to the Company's assets with the help of Google Sheets as its main database and Appsheet as a simple application for filling out reports.